Kendala dan Dukungan Program PMT Sebagai Upaya Pencegahan Stunting di Desa Duwet - Isnaini Leli; Mahatma Qurrota A’yun Iswary; Filistian Ningrum Sekar Widia Sari; Bitorian Arsyad Yanuar; Kustiarini (Society of Visual Informatics, 2025)
The Supplementary Feeding Program (PMT) is an effort to provide food for toddlers and pregnant women who are malnourished. In Duwet Village itself, there is a problem of stunting that requires the Duwet Village to implement the PMT program. However, in its implementation there are certainly obstacles. This study aims to determine the support and obstacles of the PMT (Supplementary Feeding) program in Duwet Village. The method used in this study is a qualitative descriptive method. The results show that the PMT (Supplementary Feeding) program is considered effective in preventing and overcoming stunting in Duwet Village. Stunting cases have decreased after the implementation of PMT. The implementation of PMT in Duwet Village also received support from several parties including the Wonosari Community Health Center, related health offices, and the village, although not optimal. However, in its implementation there are obstacles faced including distribution, limited budget, and minimal community information.